ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PERTAMBAHAN NILAI DI PT XYZ DENGAN MENGGUNAKAN SISTEM E-FAKTUR VERSI DEKSTOP DALAM PENINGKATAN KEPATUHAN PAJAK - Rahmanda Tasri, Naufan; Muslimin, Muslimin (Universitas Logistik dan Bisnis Internasional, 2025)
Value Added Tax (VAT) is a tax collected from the consumption of goods and services in the Customs Area which applies to Taxable Entrepreneurs (PKP). To provide significant contribution results, a maximum level of taxpayer compliance is required so that community prosperity is guaranteed. The level of taxpayer compliance can be seen from how a taxpayer can complete the calculation of the tax owed which will be remitted to the state. To support the level of taxpayer compliance, the government provides an integrated system that makes it easier for taxpayers to fulfill their tax obligations. This system is called the E-Faktur system. This research aims to analyze the calculation of Value Added Tax at PT XYZ using the Desktop version of the E-Invoice system in Improving Tax Compliance. This research uses a descriptive qualitative method using secondary data which includes invoices, NTPN, and proof of state revenue. The research results show that the E-Faktur system makes it easy to calculate and report PT XYZ's VAT so that PT XYZ has complied with all tax regulations in fulfilling its tax obligations, especially in collecting Value Added Tax.